Macroeconomic Determinants of the Indonesian Composite Stock Price Index: An ARDL Approach (2016-2025) - Siti Syefira Salsabila; Al’an Falina Rizkya; Rizke Maulina; Nuresti Supartini; Gusganda Suria Manda (Golden Ratio of Auditing Research, 2027)
This study investigates the short and long run impacts of macroeconomic variables inflation, the BI Rate, the USD/IDR exchange rate, and world gold prices on the Indonesian Composite Stock Price Index (IHSG). Utilizing 120 monthly observations from January 2016 to December 2025, this period accounts for severe market turbulences, including the early 2025 trading halts. Given the mixed integration orders I(0) and I(1)), an ARDL bounds testing framework and an Unrestricted Error Correction Model (UECM) with HC3 robust standard errors were applied. The ARDL bounds test reveals no stable long run cointegration (F"-statistic"=2.192, below the lower critical bound), indicating that macroeconomic indicators do not establish a long term equilibrium with the IHSG. Conversely, short run dynamics demonstrate that contemporaneous rupiah depreciation significantly dampens the IHSG. Lagged inflation exhibits a positive effect, while gold prices stimulate the index concurrently but induce a negative effect in the subsequent month, reflecting a delayed safe haven rotation. The BI Rate shows no significant direct impact once exchange rate dynamics are controlled. These findings imply that the IHSG is primarily driven by immediate currency shocks and commodity price pressures rather than long term macroeconomic anchoring.